Factors Influencing Traffic Compliance - Himawan, Agung (International Journal of Social and Management Studies, 2023)
This literature review study is motivated by the existence of a phenomenon that describes traffic non-compliance behavior in Indonesia by road users from time to time which is quite concerning, especially the non-adherent behavior of adolescents. This literature is intended to theoretically analyze the factors that influence traffic compliance. The literature review method was carried out on several articles obtained from google scholar, E-resources.perpusnas, LIPI, Researchgate, Indonesia OneSearch, DOAJ, Academia.edu, ScienceDirect with keywords in finding articles namely traffic compliance and youth disobedience in traffic . The results of the literature review on several articles, the authors found that there is a close relationship with the factors that influence traffic compliance. Each result found produces fifteen major themes, namely (1) Knowledge of traffic rules, (2) Self control, (3) Aggressiveness, (4) Conformity, (5) Perceived risk, (6) Role taking , (7) Age and gender, (8) The attitude of the driver, (9) Instrinsic values, values of compassion, values of usefulness and values of justice, (10) Social support, (11) Image of the Traffic Police, (12) Strict law enforcement and effective implementation of the ticket program is humane, (13) Road-worthy technical requirements for vehicles and technical requirements for road infrastructure, (14) Cultural factors, (15) Behavior thinking about other things and driving a vehicle in a tired condition. Based on the results of the literature review, it proves that there is a decrease in the number of traffic accidents, through the fulfillment of fifteen factors that can affect traffic compliance. The conclusion from the literature review is that traffic compliance has an effect on reducing the number of traffic accidents. Recommendations for this literature review can make traffic compliance a way to reduce the number of traffic accidents.